Formation of Civil Activity at School children teenagers in the Process of Out-Of-Class Activity - Aigerim Baikulova4, Dinara Sadirbekova5.Babur Rakhimov1, Kundyz Uteyeva2, Ulzharkyn Аbdigapbarova3, (Opción, 2019)
The aim of the study is to investigate the formation of civil activity at schoolchildren-teenagers in the process of out-of-class activity via methods of mathematical statistics and graphic representation of results. As a result, the school has to be the most important institute of upbringing and education of younger generation, so exactly in these conditions, it has a special role in formation and development of the Kazakhstan patriotism. In conclusion, civil activity of schoolchildren is the integral component of process of all-round development of the personality, result of socialization of the individual in the context of his national revival.